ANALISIS YURIDIS AFFIRMATIVE ACTION KUOTA 30% KETERWAKILAN PEREMPUAN DI DPRD KOTA BAUBAU - Nasrin, Nasrin; Muskur, La Ode Muhammad; Tambunan, Sahala Oschar (Jurnal Ilmu Hukum Kanturuna Wolio, 2024)
Affirmative action quota of 30% women's representation in the Indonesian Parliament is a policy taken by the Indonesian government to increase women's participation and representation in legislative institutions. This policy is motivated by the fact that women are still underrepresented in the Indonesian Parliament, even though around half of Indonesia's population are women. According to data from the Inter-Parliamentary Union (IPU) in 2021, Indonesia ranked 111th out of 193 countries in terms of women's representation in the national parliament, with only 20.4% of the total members of parliament being women. The affirmative action policy of 30% quota for women's representation in the Indonesian Parliament aims to increase women's representation in legislative institutions, so that they can better fight for women's interests and rights and strengthen democracy in Indonesia. This research aims to determine the affirmative action policy of a 30% quota for women's representation in the Baubau City DPRD. to determine the impact of the affirmative action policy of the 30% quota for women's representation not being met in Baubau City. The type of research that is suitable for the research above is normative juridical legal research. Secondary legal materials or secondary legal sources, namely legal sources that are not directly produced by institutions or parties authorized to make laws. Secondary legal materials contain interpretations, explanations, analyzes or comments on primary legal materials. Examples are law books, scientific journals, research reports, articles, theses, dissertations, translated legal documents, and so on. Tertiary legal materials or tertiary legal sources, namely legal sources that are general in nature and are usually used as reference materials in making primary and secondary legal materials. Examples are legal dictionaries, legal encyclopedias, handbooks, legal guides, legal websites, and so on.